Chemical modifications of lysozyme - Farmer, P; Farmer, P. B. (1970)
﻿ The three-dimensional structure of the glycosidase, hen egg white lysozyme, has been determined by X-ray crystallography; the molecule is roughly ellipsoidal, with a cleft running down one side, and this cleft, which is capable of accommodating up to six sugar residues (in sub-sites A-F) is known to be the site of catalytic action, glycolysis occurring between sites D and E. The only significant enzyme functional groups in this region are the carboxylic acids Asp 52 and Glu 35, and it is generally accepted that Glu 35, which is in a hydrophobic environment and which would be expected to be unionised at the optimum pH for lysozyme action, acts as a general acid catalyst in the cleavage of the glycoside. General acid catalysis alone is however not sufficient to account for the catalytic properties of lysozyme, and controversy exists over the source of the extra catalysis required. Asp 52, which has a low pK value and which would be ionised at the optimum pH for lysozyme activity, is an obvious choice of a residue which could participate in the mechanism, either by stabilising an intermediate carbonium ion by ion-pair formation, or by intramolecularly assisting expulsion of the aglycone, both after protonation of the glycosidic oxygen atom by Glu 35. However, as the best substrates for lysozyme are polysaccharides of N-acetyl glucosamine and its derivatives, it is also possible that, with these substrates, the neighbouring acetamido group could intramolecularly assist glycolysis. Although detailed studies of the glycolysis and transglycosylation reactions catalysed by lysozyme have been made, the question of whether neighbouring group participation assists in the catalytic mechanism remains unresolved. The kinetic analysis of hydrolysis of normal substrates, (for example andbeta;(1 andrarr; 4) linked polymers of N-acetyl glucosamine), is complicated by non-productive binding and transglycosylation, and use has to be made of model substrates such as aryl glycosides of N-acetyl glucosamine oligomers; although poor substrates these are hydrolysed with Michaelisandndash;Menten Kinetics, but results obtained from them are subject to the criticism that one cannot be certain that they bind exactly as, or even are subject to the same mechanism of hydrolysis as normal substrates. Modification of the enzyme rather than the substrate is therefore a more satisfactory approach, and this thesis describes the attempted conversion of aspartic acid 52 to asparagine, a modification which should not affect the accessibility of the active site, but which should enable a more definite conclusion to be made as to the degree of involvement of this residue in the catalytic mechanism. The reaction chosen for effecting this modification was that of the acid with a carbodiimide in the presence of ammonia, and in order that the modification would be specific for Asp 52 the diimide was incorporated into the compound (I) below, which was synthesised in eight stages. (I) should bind to lysozyme with its sugar residue in site C and with its C-l side chain extending down the cleft to the Asp 52 region. [For the diagram, please consult the PDF.] Reaction of lysozyme with this compound has been shown to be complex; inactivation of the enzyme was found to be independent of added nucleophile (and must therefore involve some intramolecular reaction or the irreversible attachment of the inhibitor), and a variety of products of more or less acidic nature than native enzyme was formed. The separation and purification of these modified enzymes by cation-exchange chromatography is described. The major product which was eluted before native enzyme in such a separation was unmodified at Asp 52 or Glu 35, and, as its lower rate of lysis of M. lysodeikticus cell walls than native enzyme (40andndash;50%) could be accounted for entirely by a loss of binding ability, a binding site modification is suggested for this material. The major modified enzyme of less acidic nature than native enzyme was shown to contain a catalytic site modification, and an active site peptide containing residue 52 was isolated. This residue was shown not to be aspartic acid by electrophoresis at pH 6.5, although the modification was labile to acid hydrolysis and leucine aminopeptidase digestion, both of which released aspartic acid. New methods for the separation and identification of asparagine by amino-acid analysis and on paper are described, and the modified residue 52 was shown not to be asparagine by these methods. The modification of aspartic acid 52 in lysozyme by the diimide I was shown to be associated with a loss of binding ability for small oligosaccharides, the product being completely inactive and showing no ability to bind tri-(N-acetyl)-glucosamine. Possible intramolecular reactions and modes of irreversible attachment of the inhibitor to Asp 52 are considered, and it is concluded that the latter is in all probability responsible for the inactivation of the enzyme. The Asp 52-modified enzyme has been crystallised and it is hoped that X-ray diffraction data can be obtained from the crystals, in which case the nature of the modification should be confirmed. Although the fact that the derivative does not bind substrate makes it unsuitable for investigation of the function of Asp 52 in the catalytic mechanism the fact that it contains a blocked sub-site C (which is normally the strongest binding site) means that it could be used in valuable studies of the binding of saccharide residues to other sites, and in particular to sites E and F. Preliminary evidence as to the strong binding of N-acetyl glucosamine in site E has been obtained.